The Impact of Stereotypes in Cross Cultural Communications between PMM and PNM Students - Moh. Farid Maftuh; Imam Mudofir; Muhammad Isa (International Journal of Multilingual Education and Applied Linguistics, 2025)
This study aims to describe how stereotypes occur in cross-cultural communication between PMM and PNM students and to examine their impacts on students’ achievement and interaction. A descriptive qualitative approach was employed, with data collected through observation, interviews, and questionnaires to capture both behavioral and perceptual aspects of communication. The findings reveal several key points. First, initial interactions shaped expectations and assumptions about each other’s behavior and culture. Second, stereotypes often caused miscommunication, misunderstandings, and confusion in interpreting messages. Third, they influenced group dynamics, including cooperation, participation, and conflict resolution. Fourth, students’ perceptions of identity, both personal and cultural, played a role in shaping their interactions. Fifth, the study identified both positive and negative impacts. Positive effects included enhanced Javanese language skills, increased cultural awareness, strengthened group identity, and cognitive shortcuts that facilitated understanding of others. Negative effects involved communication gaps, misinterpretation, discrimination, cultural barriers, and language difficulties. Overall, the study highlights that stereotypes in cross-cultural communication are a double-edged sword: while they can provide quick cognitive frameworks for understanding others, they can also impede effective communication and collaboration. These findings emphasize the importance of cultural sensitivity, awareness, and reflective practices in multicultural student interactions to maximize learning and minimize conflicts.